Structural Characteristics of Developed Sustainable Lime-Straw Composite - Sajid Kamil Zemam; Sa'ad Fahad Resan; Musab Sabah Abed (Salehan Institute of Higher Education, 2019)
Construction materials made of renewable resources have promising potential given their low cost, availability, and environmental friendliness. Although hemp fibers are the most extensively used fiber in the eco-friendly building sector, their unavailability hinders their application in Iraq. This study aimed to overcome the absence of hemp fiber in Iraq and develop a new sustainable construction material, strawcrete, by using wheat straw and traditional lime as the base binder. A comparable method of developing hempcrete was established. The experimental program adopted novel Mixing Sequence Techniques (MSTs), which depended on changing the sequence of mixed material with fixed proportions. The orientation of the applied load and the specimen’s aspect ratio were also studied. The mixing proportion was 4:1:1 (fiber/binder/water) by volume. Results showed that the developed strawcrete had a dry unit weight ranging from 645 kg/m3 to 734 kg/m3 and a compressive strength ranging from 1.8 MPa to 3.8 MPa. The enhanced physical and strength properties varied with the MST and loading orientation. The properties of the developed hempcrete were compared with those of strawcrete.